2012
DOI: 10.1017/s0033291712000694
|View full text |Cite
|
Sign up to set email alerts
|

Is there change in intelligence quotient in chronically ill schizophrenia patients? A longitudinal study in twins discordant for schizophrenia

Abstract: Patients with schizophrenia in the chronic phase of the disease, but not the discordant co-twins, show a lack of increase in IQ, which is probably due to environmental (non-genetic) factors related to the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Apart from this, deficits in global measures of cognition such as intelligence are common in SZ patients (74, 75). On the other side, it is a well-established finding that IQ levels do not change over the course of illness and that lower IQ is a stable trait in patients suffering from SZ (7678). Furthermore, variables such as education, occupation, and age can contribute significantly to IQ values (79).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, deficits in global measures of cognition such as intelligence are common in SZ patients (74, 75). On the other side, it is a well-established finding that IQ levels do not change over the course of illness and that lower IQ is a stable trait in patients suffering from SZ (7678). Furthermore, variables such as education, occupation, and age can contribute significantly to IQ values (79).…”
Section: Discussionmentioning
confidence: 99%
“…Using a twin design, Hedman et al . (2012) reported a lack of increase in IQ in patients, not in co-twins, indicating that in chronically ill patients environmental factors implicated in the disease are associated with a lack of IQ improvement over time.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Cognitive deficits constitute a core symptom of schizophrenia, 16 with general intelligence already affected prior to onset of psychotic symptoms, 17 declining after the first psychotic episode, 18 and lacking normal gain in global cognitive abilities over time. 19,20 The intelligence quotient (IQ) is one of the most heritable cognitive phenotypes, with ~80% of the variance explained through additive genetics. 21 Using a discordant twin design, it was shown that schizophrenia and IQ share a partially overlapping genetic background.…”
Section: Introductionmentioning
confidence: 99%